1988
DOI: 10.1039/c39880001439
|View full text |Cite
|
Sign up to set email alerts
|

Novel ferrocene diesters with liquid-crystal properties

Abstract: A series of bis-(4-alkoxy-4'-biphenyl)ferrocene 1 ,I '-diesters (1) has been synthesized; three compounds in this homologous series exhibit liquid-crystal phases.Compounds which display liquid-crystal properties typically possess a rod-or disc-like core and long, flexible alkyl chains. Liquid-crystal compounds containing transition metals have recently attracted special attention because the transitionmetal centre offers the appealing prospects of imparting unique optical, magnetic and electrical properties as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The early period of this research mainly was aimed at bringing ferrocene to the polymer because of its excellent aromatic character and thermal stability at temperatures over 500°C. Several reports [61][62][63][64][65][66] are dealing with ferrocene esters. It is simply a part of the mesogen.…”
Section: Ferrocene-containing Liquid Crystalline Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The early period of this research mainly was aimed at bringing ferrocene to the polymer because of its excellent aromatic character and thermal stability at temperatures over 500°C. Several reports [61][62][63][64][65][66] are dealing with ferrocene esters. It is simply a part of the mesogen.…”
Section: Ferrocene-containing Liquid Crystalline Polymersmentioning
confidence: 99%
“…26). Generally, most of the LC ferrocenes have complicated structures, i.e., they have three aromatic rings in the mesogen unit [71,99], and two flexible long chains [100,101]. Such complexity sometimes prevents orderly molecular packing [102][103][104].…”
Section: Ferrocene Moieties In Side-chain Liquid Crystalline Polymersmentioning
confidence: 99%
“…The ferrocene moiety in the compound, however, is an appendage to a mesogenic unit rather than being in the core of the molecule. We have recently synthesized a series of ferrocene diesters which have the ferrocene moiety at the centre of the molecule [6]. Three of the compounds in this homologous series exhibit mesomorphic properties.…”
Section: Introductionmentioning
confidence: 99%
“…1. Only three ferrocene derivatives from the reported series [14] (n 4 ± 11) show mesomorphic behaviour ( Fig. 1): the compounds with n 5 and 6 exhibit a monotropic smectic C (SmC) phase in a narrow temperature interval, while the compound with n 11 gives rise to a monotropic smectic A (SmA) phase.…”
mentioning
confidence: 97%
“…Historically, the ferrocene 1,1'-diesters bis(4'-alkoxy-[1,1'-biphenyl]-4-yl) ferrocene-1,1'-dicarboxylates were reported as the first mesogenic ferrocene derivatives [14]. X-Ray diffraction studies indicated that these compounds adopt a −transoid× conformation (−S× shape) in the crystalline and mesomorphic states [15], which approximately corresponds to the pseudo-para substitution pattern in paracyclophanes.…”
mentioning
confidence: 98%